1995
DOI: 10.1103/physrevb.52.15607
|View full text |Cite
|
Sign up to set email alerts
|

Influence of next-nearest-neighbor electron hopping on the static and dynamical properties of the two-dimensional Hubbard model

Abstract: Comparing experimental data for high-T, cuprate superconductors with numerical results for electronic models, it is becoming apparent that a hopping along the plaquette diagonals has to be included to obtain quantitative agreement. However, the values for t discussed in the literature were obtained comparing theoretical results in the weak-coupling limit with photoemission data and band-structure calculations. The goal of this paper is to study how t gets renormalized as the interaction between electrons, U, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
57
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 39 publications
16
57
0
Order By: Relevance
“…These features are qualitatively consistent with the inelastic neutron scattering for La 2−x Sr x CuO 4 [ 75,76] and Nd 2−x Ce x CuO 4−y [ 79]. The same result for the electron-doped cuprates has been reported by the numerical studies on the Hubbard model [ 16,426] and t-J model [ 427].…”
Section: Magnetic Propertiessupporting
confidence: 88%
“…These features are qualitatively consistent with the inelastic neutron scattering for La 2−x Sr x CuO 4 [ 75,76] and Nd 2−x Ce x CuO 4−y [ 79]. The same result for the electron-doped cuprates has been reported by the numerical studies on the Hubbard model [ 16,426] and t-J model [ 427].…”
Section: Magnetic Propertiessupporting
confidence: 88%
“…Numerous analytical and numerical calculations, however, have demonstrated that this degeneracy is an artifact of the mean-field treatment [5,29,[33][34][35] -the actual fermionic dispersion possesses a maximum at (π/2, π/2) and symmetry related points. Recent photoemission experiments on Sr 2 CuO 2 Cl 2 confirmed this result and in addition have shown that the dispersion near the top of the valence band is nearly isotropic around (π/2, π/2) [26,27].…”
Section: B Resonance Near ω (1) Resmentioning
confidence: 99%
“…The criteria used here to obtain the most probable locus of the FS from numerical n(q) data are two: (a) find the values of q where n(q) ≈ 0.5 [11] and (b) find the values of q where n(q) changes the most rapidly [20]. For the case of t ′ /t=-0.25 we have observed that both methods provide similar results in the regions close to the diagonal direction in the Brillouin zone, but substantial differences were observed close to the (0, π) and (π, 0) points.…”
Section: B Fermi Surfacementioning
confidence: 99%